The Influence of Student Creativity, Instructional Media, Teaching Style, Family Environment, and Study Hours on the Learning Outcomes of 12th-Grade Students in Home Economics at SMKN 1 Simpang Alahan Mati - Nurlatifah Nurlatifah; Jolianis Jolianis; Lovelly Dwinda Dahen (Darul Yasin Al Sys, 2026)
This study is motivated by the relatively low learning outcomes of eleventh-grade students in the PKK subject at SMK Negeri 1 Simpang Alahan Mati, which are presumed to be influenced by internal and external factors, including student creativity, instructional media, teaching style, family environment, and study time. This study aims to examine the partial and simultaneous effects of these variables on students’ learning outcomes. A quantitative approach with an associative-causal design was employed. The population comprised 105 students, and the sample was selected using proportional random sampling. Data were collected through questionnaires, documentation, and observation, and analyzed using multiple linear regression with the assistance of statistical software. The findings indicate that student creativity, instructional media, teaching style, family environment, and study time each have a significant partial effect on learning outcomes. Simultaneously, all independent variables significantly influence learning outcomes and provide a substantial contribution to the dependent variable. These findings demonstrate that improving students’ learning outcomes requires the integrated optimization of both internal and external learning factors. The study contributes to educational practice by emphasizing the importance of creative teaching strategies, adequate instructional media, supportive family environments, and effective study-time management in strengthening students’ academic performance.